Unilateral Frontalis Suspension With Silicone Sling Without Levator Extirpation in Congenital Ptosis With Marcus Gunn Jaw Winking Synkinesis. Issue 4 (July 2020) - Shah, Gaurav; Khurana, Deepika; Das, Sima; Tiple, Sweety; Honavar, Santosh G.
Abstract : Purpose: To evaluate the efficacy of unilateral tarso-frontalis silicone sling without levator extirpation or disinsertion in dampening the jaw wink in patients with congenital ptosis associated with Marcus Gunn Jaw Winking synkinesis phenomenon. Methods: Retrospective review of medical records of all patients of congenital ptosis with moderate to severe Marcus Gunn jaw winking synkinesis who underwent unilateral tarsofrontal silicone sling surgery without extirpation of the levator muscle were retrospectively reviewed. Data were collected about the pre- and the postoperative severity of the ptosis and the amount of Marcus Gunn jaw winking excursion. Results: Twenty-three patients were included in the study. Mean postoperative follow up duration was 31.2 (range 6–208) weeks. The severity of the preoperative jaw wink was mild (<2 mm excursion) in 0 patient, moderate (2–5mm) in 15 (65%) patients, and severe (>5 mm eyelid excursion) in 8 (35%) patients. Postoperatively, 20 (87%) patients had mild residual jaw wink, 3 (13%) patients had moderate jaw wink and none of the patient had severe residual jaw wink. Conclusion: Unilateral tarsofrontal silicone sling without disinsertion or extirpation of the levator can reduce the severity of the jaw wink excursion in patients with congenital ptosis with moderate to severe preoperative Marcus Gunn jaw winking synkinesis. Abstract : Unilateral frontalis suspension without levator extirpation can cause improvement in the severity of jaw wink in patients with congenital ptosis with Marcus Gun Jaw winking synkinesis.